Project activity in the formation of subject competencies - Yanuschik, Olga V.; Ustinova, Irina G.; Imas, Olga Nikolaevna; Rozhkova, Svetlana V. (Mobility for smart cities and regional development - challenges for higher education : proceedings of the 24th International conference on interactive collaborative learning (ICL2021))
The project-based learning has long established itself as one of the most stimulating methods of mastering the educational program. However, to study in depth of mathematical disciplines, project tasks must be specifically formulated for the topic being studied. The purpose of this work is to study the methodological relationship between the declared projects and the studied topic of mathematics, as well as a comparative analysis of the results of the development of three mathematical disciplines using the project method and without it. The work on the projects has been carried out for three years at our university and it is aimed at activating the independent cognitive activity of students. In 2018-2019, these were applied and educational projects, the topics for which were selected by teachers. In 2019-2020, students were given the right to independently choose a project topic based on their scientific interests and develop it. In one experimental group, students had the opportunity to consult with the teacher to find a solution to the project problem, in the other such an opportunity was not available. The results of both groups were roughly the same. The conclusion that we came to as a result of this work: project activity increases the horizons of students and allows us to see interdisciplinary connections. Project activity is more effective only if the student works closely with the teacher.